¿Por qué vivimos más? Descomposición por causa de la esperanza de vida española de 1980 a 2009 - García-González, Juan Manuel (Revista Española de Investigaciones Sociológicas, 2017)
Este trabajo describe y explica de forma interdisciplinar las tendencias recientes de la esperanza de vida al nacimiento en España. Se utilizan dos metodologías: regresión lineal segmentada y descomposición de la esperanza de vida. El estudio consta de tres partes. Primero, se describen los factores demográficos que se encuentran tras el aumento de más de 40 años en la esperanza de vida al nacimiento de 1910 a 2009. Segundo, se analiza el efecto que el cambio de la mortalidad, por causa de muerte, en mayores de 65 años ha tenido en esa esperanza de vida en 1980-2009. Y tercero, se aportan las causas socioepidemiológicas que hay detrás de dicho incremento. Se concluye que ese aumento se debe principalmente a la reducción de la mortalidad en las edades avanzadas y a la disminución de la mortalidad por enfermedades cardiovasculares.
Why Do we Live Longer? Decomposition by Cause of Life Expectancy in Spain between 1980 and 2009
This paper describes and explains the recent trends in life expectancy at birth in Spain from an interdisciplinary perspective. It is based on two methods: segmented linear regression, and decomposition of life expectancy. The study consists of three sections. First, a description is provided of the demographic factors that explain the increase in the life expectancy at birth of the Spanish population from 1910 to 2009, which is in excess of 40 years. Second, the effect that changes in mortality have had on life expectancy at birth during 1980-2009 is analysed by cause of death of the population aged 65 and above. And third, the social and epidemiological causes underlying that increase are described. It is concluded that the increase of life expectancy at birth in Spain is mainly due to the reduction of mortality at advanced ages and a decrease in cardiovascular mortality
Keywords: cambio social; causas de muerte; esperanza de vida; longevidad; mortalidad; social change; causes of death; life expectancy; longevity; mortality; JCR; Scopus